Indian philosophy : an introduction to Hindu and Buddhist thought - King, Richard, 1966- (Edinburgh : Edinburgh University Press, 1999)
What is Indian Philosophy? Why has India been excluded from the history of philosophy? Richard King provides an introduction to the main schools of Hindu and Buddhist thought, emphasising the living history of interaction and debate between the various traditions. The book outlines the broad spectrum of Indian philosophical schools and questions prevailing assumptions about the 'mythical', ahistorical and 'theological' nature of Indian thought. -- Provided by publisher.
Includes bibliographical references (pages 246-254) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Hinduism; Buddhism; Philosophy, Indic; Buddhism; Hindouisme; Bouddhisme; Philosophie de l'Inde.; Hinduism; Buddhism; PHILOSOPHY -- Hindu; PHILOSOPHY / Eastern; Buddhism; Hinduism; Philosophy, Indic; Buddhismus; Hinduismus; Philosophie; Indische filosofie; Hindoeïsme.; Boeddhisme; Philosophy; Philosophy & Religion